Current surgical treatment of intermediate risk differentiated thyroid cancer: a systematic review. Issue 2 (1st February 2021) - Guo, Michael Y.; Wiseman, Jacob J.; Wiseman, Sam M.
ABSTRACT: Introduction : Surgical treatment of thyroid cancer has become less aggressive but for many patients, the threshold for performing total thyroidectomy (TT), as opposed to thyroid lobectomy (TL), has remained unclear. Current American Thyroid Association (ATA) guidelines encourage more individualization of treatment options, which necessitates explicit review of the pros and cons of the different options with patients. Areas covered : This review focuses on the extent of surgery for treatment of intermediate-risk differentiated thyroid cancer, restricted to relevant literature available after publication of the 2015 ATA guidelines. Expert opinion : Dynamic risk-stratification facilitates a tailored approach when deciding on the extent of surgery for thyroid cancer. Treatment with TT allows for a lower recurrence risk, a simpler follow-up regimen, and treatment with adjuvant post-operative radioactive iodine. Treatment with TL has a lower associated risk of complications and avoidance of lifelong thyroid hormone replacement but has a significant risk of requiring a completion thyroid lobectomy (CT). Overall, treatment with TL and TT have comparable survival outcomes, but TL is the more cost-effective option. Larger cancer size is correlated with worse clinical outcomes, and numerous subgroup analyses have shown poorer outcomes for cancers with a diameter that is 2–4 cm compared to 1–2 cm.